Penerapan Media Kahoot Berbasis Gamifikasi untuk Meningkatkan Pemahaman Siswa dalam Pembelajaran Perkalian dan Pembagian Kelas 3 MI Marinjung - Rismawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' understanding of multiplication and division concepts in third-grade elementary school/madrasah classrooms by utilizing gamification-based Kahoot media. The researcher employed Classroom Action Research (CAR), which emphasizes detailed investigation at each stage. The subjects of this study were 23 third-grade students at MI Marinjung. Data were collected through pre-test and post-test scores, student and teacher observations, as well as documentation. The test results indicated that during the pre-cycle stage, the percentage of students meeting the Minimum Mastery Criterion (KKM) was 34.34%. In cycle 1, following the treatment, the mastery percentage increased to 56.52%. By cycle 2, the percentage of students reaching the KKM rose significantly to 82.60%. Furthermore, the student observation scores improved from 77.48% in cycle 1 to 88.48% in cycle 2. Consequently, it can be concluded that the use of gamification-based Kahoot media can enhance students' understanding in learning multiplication and division.